BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

A second update to the checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; G. Calvia; et al. (Plant Biosystems, 2024)

A second update to the checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; M. Castello; et al. (Plant Biosystems, 2024)

Establishing the Foundation for the Global Observing System for Marine Life - Erin V. Satterthwaite; Nicholas J. Bax; Patricia Miloslavich; Lavenia Ratnarajah; Gabrielle Canonico; Daniel Dunn; Samantha E. Simmons; Roxanne J. Carini; Karen Evans; Valerie Allain; Ward Appeltans; Sonia Batten; et al. (Frontiers in Marine Science, 2021)
Maintaining healthy, productive ecosystems in the face of pervasive and accelerating human impacts including climate change requires globally coordinated and sustained observations of marine biodiversity. Global coordination is predicated on an understanding of the scope and capacity of existing monitoring programs, and the extent to which they use standardized, interoperable practices for data management. Global coordination also requires identification of gaps in spatial and ecosystem coverage, and how these gaps correspond to management priorities and information needs. We undertook such an assessment by conducting an audit and gap analysis from global databases and structured surveys of experts. Of 371 survey respondents, 203 active, long-term (>5 years) observing programs systematically sampled marine life. These programs spanned about 7% of the ocean surface area, mostly concentrated in coastal regions of the United States, Canada, Europe, and Australia. Seagrasses, mangroves, hard corals, and macroalgae were sampled in 6% of the entire global coastal zone. Two-thirds of all observing programs offered accessible data, but methods and conditions for access were highly variable. Our assessment indicates that the global observing system is largely uncoordinated which results in a failure to deliver critical information required for informed decision-making such as, status and trends, for the conservation and sustainability of marine ecosystems and provision of ecosystem services. Based on our study, we suggest four key steps that can increase the sustainability, connectivity and spatial coverage of biological Essential Ocean Variables in the global ocean: (1) sustaining existing observing programs and encouraging coordination among these; (2) continuing to strive for data strategies that follow FAIR principles (findable, accessible, interoperable, and reusable); (3) utilizing existing ocean observing platforms and enhancing support to expand observing along coasts of developing countries, in deep ocean basins, and near the poles; and (4) targeting capacity building efforts. Following these suggestions could help create a coordinated marine biodiversity observing system enabling ecological forecasting and better planning for a sustainable use of ocean resources.

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

An updated checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; N. M. G. Ardenghi; E. Banfi; L. Celesti-Grapow; A. Albano; A. Alessandrini; G. Bacchetta; S. Ballelli; M. Bandini Mazzanti; G. Barberis; et al. (Plant Biosystems, 2018)

Fungi as a toolbox for sustainable bioremediation of pesticides in soil and water - F. Spina; G. Cecchi; A. Landinez-Torres; L. Pecoraro; F. Russo; B. Wu; L. Cai; X. Z. Liu; S. Tosi; G. C. Varese; M. Zotti; A. M. Persiani (Plant Biosystems, 2018)

An updated checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Albano; A. Alessandrini; N. M. G. Ardenghi; G. Astuti; G. Bacchetta; S. Ballelli; E. Banfi; G. Barberis; L. Bernardo; et al. (Plant Biosystems, 2018)

Improvement of the esca index for the evaluation of ecological quality of coralligenous habitat under the european framework directives - L. PIAZZI; P. GENNARO; E. CECCHI; F. SERENA (Mediterranean Marine Science, 2015)
The ESCA (Ecological Status of Coralligenous Assemblages) index was recently developed to evaluate the ecological quality of coralligenous habitat. The study aims to improve the first index proposal through testing response to different sources of anthropogenic pressures and optimizing the sampling effort. ESCA was calculated on 14 sites and tested against a gradient of human pressures. Moreover, the main scales of spatial variability of assemblages were evaluated and values of index obtained with different sampling designs were compared. Results showed that studied sites resulted in high, good or moderate ecological status, according to an increasing gradient of the anthropization level. Values of ESCA index obtained with different methods have been compared and photographic method provides EQR values lower than destructive method. Spatial variability of assemblages was higher at large and small scales than at intermediate ones. Two locations for each study site and 20 replicated samples for each location may be consider the best sampling combination providing reliable values of ESCA index for the evaluation of ecological quality of coralligenous assemblages.

Synopsis of Boraginaceae subfam. Boraginoideae tribe Boragineae in Italy - L. Cecchi; F. Selvi (Plant Biosystems, 2015)

A synopsis of Boraginaceae subfam. Hydrophylloideae and Heliotropioideae in Italy - L. Cecchi; F. Selvi (Plant Biosystems, 2014)

Impact of 2003 heat waves on aerobiological indices of allergenic herbaceous family pollen season in Tuscany (Italy) - F. Natali; L. Cecchi; T. Torrigiani Malaspina; F. Barbano; S. Orlandini (Aerobiologia, 2013)

Habitat heterogeneity promotes the coexistence of exotic seaweeds - L. Tamburello; L. Benedetti-Cecchi; L. Masini; F. Bulleri (Oecologia, 2013)

Evolutionary dynamics of serpentine adaptation in Onosma (Boraginaceae) as revealed by ITS sequence data - L. Cecchi; A. Coppi; F. Selvi (Plant Systematics and Evolution, 2011)

The effects of large-scale atmospheric fields on the cypress pollen season in Tuscany (Central Italy) - A. Dalla Marta; D. Grifoni; T. Torrigiani Malaspina; L. Cecchi; F. Barbano; M. Mancini; S. Orlandini (Aerobiologia, 2011)

Revisiting the effect of referral bias on the clinical spectrum of infective endocarditis in adults - Z. A. Kanafani; S. S. Kanj; C. H. Cabell; E. Cecchi; A. Oliveira Ramos; T. Lejko-Zupanc; P. A. Pappas; H. Giamerellou; D. Gordon; C. Michelet; P. Muñoz; O. Pachirat; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Comparison of the structure and composition of bacterial communities from temperate and tropical freshwater ecosystems - Jean‐F. Humbert; Ursula Dorigo; Philippe Cecchi; Brigitte Le Berre; Didier Debroas; Marc Bouvy (Environmental Microbiology, 2009)
Summary We used a partial 16S rRNA sequencing approach to compare the structure and composition of the bacterial communities in three large, deep subalpine lakes in France with those of communities in six shallow tropical reservoirs in Burkina Faso. Despite the very different characteristics of these ecosystems, we found that their bacterial communities share the same composition in regard to the relative proportions of the different phyla, suggesting that freshwater environmental conditions lead to convergence in this composition. In the same way, we found no significant difference in the richness and diversity of the bacterial communities in France and Burkina Faso. We defined core and satellite operational taxonomic units (OTUs) (sequences sharing at least 98% identity) on the basis of their abundance and their geographical distribution. The core OTUs were found either ubiquitously or only in temperate or tropical and subtropical areas, and they contained more than 70% of all the sequences retrieved in this study. In contrast, satellite OTUs were characterized by having a more restricted geographical distribution and by lower abundance. Finally, the bacterial community composition of these freshwater ecosystems in France and Burkina Faso was markedly different, showing that the history of these ecosystems and regional environmental parameters have a greater impact on the relative abundances of the different OTUs in each bacterial community than the local environmental conditions.

Beef Traceability Using Molecular Methodologies - G. Filippini; V. Cetica; R. Ciampolini; M. Biagetti; F. Cecchi; E. Mazzanti; E. Ciani; C. Sebastiani; G. Venditti (Veterinary Research Communications, 2006)

Dermatophytes isolated from symptomatic dogs and cats in Tuscany, Italy during a 15-year-period - F. Mancianti; S. Nardoni; S. Cecchi; M. Corazza; F. Taccini (Mycopathologia, 2003)

Acidogenic fermentation of source separated mixtures of vegetables and fruits wasted from supermarkets - P. Traverso; P. Pavan; D. Bolzonella; L. Innocenti; F. Cecchi; J. Mata-Alvarez (Biodegradation, 2000)

Crossbridge kinetics in single frog muscle fibres in presence of ethylene glycol - M. A. Bagni; G. Cecchi; B. Colombini; F. Colomo (Journal of Muscle Research and Cell Motility, 2000)

The interplay of physical and biological factors in maintaining mid-shore and low-shore assemblages on rocky coasts in the north-west Mediterranean - L. Benedetti-Cecchi; F. Bulleri; F. Cinelli (Oecologia, 2000)

Sarcomere tension–stiffness relation during the tetanus rise in single frog muscle fibres - M. A. Bagni; G. Cecchi; B. Colombini; F. Colomo (Journal of Muscle Research and Cell Motility, 1999)

Force responses to fast ramp stretches in stimulated frog skeletal muscle fibres - M. A. Bagni; G. Cecchi; E. Cecchini; B. Colombini; F. Colomo (Journal of Muscle Research and Cell Motility, 1998)